KETELADANAN GURU DAN INOVASI PENDIDIKAN ISLAM: (Sebuah Kajian di Pondok Pesantren DDI Mangkoso Barru) - Wahid, Zakaria; Muhammad Amri; Syamsuddin; Muhammad Nur Korompot (ISTIQRA: Jurnal Hasil Penelitian, 2024)
This research aims to understand teachers’ perceptions of exemplary behavior in instilling Islamic values at DDI Mangkoso Islamic Boarding School in Barru Regency. The study employs a qualitative approach with a psychological orientation. Both primary and secondary data sources are utilized, and data collection methods include observation, interviews, and documentation. Data analysis involves data reduction, data display, and conclusion. The findings reveal that teachers employ a three-stage process, value transformation, value transaction, and value internalization in imparting Islamic values. Significant challenges arise from the varying characters of students in understanding and applying these values, necessitating innovative approaches beyond conventional methods employed by teachers. This calls for flexibility and adaptability in the teaching process. The implications of this research provide insights and recommendations to enhance the quality of DDI Mangkoso Islamic Boarding School in Barru Regency moving forward.